The Impact of Corporate Governance on Earnings Management: The Case Of Pakistan Textile Industry - Shahzad Ahmad; Asad Sarfaraz Khan; Dr. Muhammad Zahid (Journal of Business & Tourism, 2021)
Due to globalization and expansion in the world markets, the sensitivity of investor’s confidence has become a challenge especially in the wake of issues related to stock prices, earnings management (EM), the stability of income levels and corporate governance (CG) application. This study aims to explore the usefulness of four traits of corporate governance mechanism in constraining earnings management activities. By using five years’ observations of 109 textile companies listed on Pakistan Stock Exchange (PSX) for the period 2013-2017. Traits comprising of board size, gender diversity, board experience and qualification of board member are analyzed using Ordinary Least Square (OLS). Results of the study submit that board experience; finance qualification and business qualification have a negative significant impact on EM thus contends that experienced board members having business and finance qualification discourage earnings manipulation. While, positive and significant impact of board size on earnings management is an indication of loss of control due to its large size. Moreover, gender diversity and chartered accountancy are found irrelevant to EM in our case.